Semantics, analytics, visualization : enhancing scholarly data : second International Workshop, SAVE-SD 2016, Montreal, QC, Canada, April 11, 2016, Revised selected papers /: enhancing scholarly data : second International Workshop, SAVE-SD 2016, Montreal, QC, Canada, April 11, 2016, Revised selected papers. (2016) - Unknown
No abstract available